ANALISIS MODEL KURIKULUM BERBASIS KARAKTER DALAM UPAYA MENCEGAH BULLYING PADA SISWA SDN BANYUBULU 3 PROPPO PAMEKASAN - Firdaus, Yuliana Izdihar (CV. Jendela Gagasan, 2024)
This research aims to analyze the character-based curriculum model in efforts to prevent bullying, bullying prevention curriculum in elementary schools. This research is research using qualitative methods and also through a literature study approach that analyzes the emphasis on a descriptive approach. The data sources used come from scientific articles published in the last 10 years. Articles were collected via Google Scholar with the keywords character education, bullying, elementary school. This data was also obtained through observation, interviews with teachers and parents as well as students who experienced bullying at school. The results of this research are The Systematic Action-Research Curriculum Model which is considered to be able to be used as a character-based curriculum development so that children's bullying behavior can be overcome. The Systematic Action-Research Model can be used through evaluation and improvement planning activities, where each stage can be carried out regularly.